Private/Public in 18th-Century Scandinavia - Nauman, Sari; Vogt, Helle (Cultures of Early Modern Europe, 2022)
An interdisciplinary exploration of the emerging notion of the 'private' in relation to the public in 18th-century Scandinavia.